An Updated Review of Iclaprim: A Potent and Rapidly Bactericidal Antibiotic for the Treatment of Skin and Skin Structure Infections and Nosocomial Pneumonia Caused by Gram-Positive Including Multidrug-Resistant Bacteria. (6th January 2018) - Huang, David B; Strader, Catherine D; MacDonald, James S; VanArendonk, Mark; Peck, Richard; Holland, Thomas
Abstract: New antibiotics are needed because of the increased morbidity and mortality associated with multidrug-resistant bacteria. Iclaprim, a bacterial dihydrofolate reductase inhibitor, not currently approved, is being studied for the treatment of skin infections and nosocomial pneumonia caused by Gram-positve bacteria, including multidrug-resistant bacteria. Iclaprim showed noninferiority at –10% to linezolid in 1 of 2 phase 3 studies for the treatment of complicated skin and skin structure infections with a weight-based dose (0.8 mg/kg) but did not show noninferiority at –10% to linezolid in a second phase 3 study. More recently, iclaprim has shown noninferiority at –10% to vancomycin in 2 phase 3 studies for the treatment of acute bacterial skin and skin structure infections with an optimized fixed dose (80 mg). A phase 3 study for the treatment of hospital-acquired bacterial and ventilator-associated bacterial pneumonia is upcoming. If, as anticipated, iclaprim becomes available for the treatment of skin and skin structure infections, it will serve as an alternative to current antibiotics for treatment of severe infections. This article will provide an update to the chemistry, preclinical, pharmacology, microbiology, clinical and regulatory status of iclaprim.